Efektifitas Media Pembelajaran Melalui Model Discovery Learning terhadap Minat dan Hasil Belajar Peserta Didik SDN 193 Pekanbaru - Hayatun Najmi; Yayuk Cicilia; Rian Vebrianto (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This study aims to determine the effect of the use of science learning media on discovery learning models on the interests and achievements of student learning outcomes in alternative energy materials. This study uses an experimental method, the sample consists of 2 classes, cognitive learning achievement data using tests, affective aspects of learning achievement using a questionnaire, hypothesis testing using the right-hand t-test. The data analysis technique used is the n-gain test and independent sample t-test using SPSS version 16.0. The results showed that students who were taught using science learning media on discovery learning models gave a good influence on students' interest and learning achievement better than students who were taught the lecture method. Students with high learning interest produce better average achievement than students with low learning interest, and there is an increase in student learning achievement using learning media